Opportunities and challenges for rail transport of solid wood biofuel - Flodén, Jonas (European Journal of Transport and Infrastructure Research, 2016)
The use of solid biofuel for energy in heating plants has increased drastically during the last decades. This substantial and increasing demand has placed focus on delivering biofuel to the plants, as logistics issues are considered one of the key challenges for further increased use of biofuel. Problems in sourcing enough fuel locally due to the increasing size of power plants and environmental concerns has sparked an interest in using multimodal road-rail transport as a cost effective and environmentally friendly way of long-haul transport. A case study is performed at a Swedish district heating plant to investigate the potential of introducing multimodal transport. Extensive calculations are performed in the design and operation of a multimodal system, showing both costs and CO2 emissions. This is analysed in relation to key logistical challenges in the industry. A best case scenario is identified. Conclusions are that the potential for multimodal transport is greatest among the largest plants with large volumes to achieve high resource utilisation of the transport equipment. A shift from road to multimodal transport is facilitated by that a large share of the current road transport flows already pass through a terminal, which improves multimodal transport competitiveness against road transport as this reduced the cost difference. This study leads to better understanding of the strengths and weaknesses of multimodal biofuel transport and has practical implications for anyone in the process of designing such systems.